Revealing “Essentials of Goryeo History”: Historical Record Mirroring the Internal Administration during the Reign of King Taejo of Goryeo (918-943) - Jannoom, Pornpan (Journal of Social Sciences Naresuan University, 2022)
This research paper aims to study the course of government administration within the realm of Goryeo in the reign of King Taejo between 918-943 by examining the historical events recorded in the Korean translation and version of Goryeosa Jeolyo. The research and analysis of the activities in this narrative classified the courses of the internal government administration into three dimensions; 1) structural governance, 2) socio-economic, and 3) religion and faith. These reflect King Taejo's s efforts to enhance the stability of the political, social, and royal institutions as a significant foothold of internal governance amid the turning edge from the later Three Kingdoms period to a new unification of the Korean peninsula under the governance of Goryeo. Moreover, the unification success resulted in the succession of the territorial legacy on the peninsula to present Korea. In addition, the study of the state formation guides the historical understanding of Goryeo as the kingdom bridging between the ancestral kingdoms of Goguryeo and Goryeo.